Youth-serving organizations' inclusivity of LGBTQ newcomers in Canada—A content analysis. Issue 3 (3rd July 2021) - Flett, Joseph
Abstract: For LGBTQ newcomer youth lacking support at home and in school, youth-serving organizations provide various services and socialization that can effectively address their challenges. In a two stage content analysis, this study explored LGBTQ newcomer inclusivity in 39 youth-serving organizations in Toronto and Vancouver, as well as programs and services offered to this subpopulation specifically. Stage 1 findings demonstrate that few organizations displayed inclusion of, and supports for, LGBTQ newcomers. Stage 2 findings show that programs and services offered to this subpopulation can be categorized into four themes: cultural and linguistic sensitivity, skills development and education, socialization and community connections, and health and well-being. Recommendations for best practices are discussed.